PERSEPSI MASYARAKAT TERHADAP BERITA EKSPLOITASI ANAK DI BIMA (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2021)
This study aims to 1) identify public knowledge of child exploitation news in Bima, and 2) determine public attitudes towards child exploitation news in Bima.This research is a quantitative research with quantitative descriptive research methods. Data collection techniques in this study were questionnaires and documentation. The sample used in this study is the community in Sambianae Village who reads the news of child exploitation, totaling 100 respondents. The sample was determined by using a non-probability technique with an incidental sampling method. The data processing technique used in this research is descriptive analysis.The results of this study are: 1) The level of public knowledge of the news of child exploitation in Bima is in the high category as many as 21 respondents with a percentage of 21%, the level of public knowledge in the medium category is 57 respondents with a percentage of 57%, and the level of public knowledge in the low category as many as 22 respondents with a percentage of 22%. 2) The public's attitude towards news of child exploitation in Bima is in the very interested category having a percentage of 42%, 50% in the moderately interested category, and 8% in the disinterested category.The implication of this research is that people can make news as a source of information and digest each news well, so that the news can be used as learning and one of the guidelines for action. The researcher also hopes that this research can be used as a source of data for similar research and that further research will be carried out based on other factors with more varied variables, sample sizes, and indicators.